2021
DOI: 10.1002/gcc.23019
|View full text |Cite|
|
Sign up to set email alerts
|

Novel EWSR1::UBP1 fusion expands the spectrum of spindle cell rhabdomyosarcomas

Abstract: Over the last decade, the development of next‐generation sequencing techniques has led to the molecular dismantlement of adult and pediatric sarcoma, with the identification of multiple gene fusions associated with specific subtypes and currently integrated into diagnostic classifications. In this report, we describe and discuss the identification of a novel EWSR1‐UBP1 gene fusion in an adult patient presenting with multi‐metastatic sarcoma. Extensive pathological, transcriptomic, and genomic characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The clinical course of the patient described above who responded to radiotherapy followed by ALK inhibition also suggests that these tumors have reduced DNA repair capacity 51 . Zein et al reported a patient with RMS carrying an EWSR1-UBP1 fusion, which seems to be a variant of EWSR1-TFCP2, as TFCP2 and UBP1 belong to the same transcription factor family, have high sequence homology, and share the same domain structure 59 . This patient responded to a lung cancer regimen that included carboplatin, which is not a standard in RMS, but progressed on subsequent maintenance therapy with pembrolizumab 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical course of the patient described above who responded to radiotherapy followed by ALK inhibition also suggests that these tumors have reduced DNA repair capacity 51 . Zein et al reported a patient with RMS carrying an EWSR1-UBP1 fusion, which seems to be a variant of EWSR1-TFCP2, as TFCP2 and UBP1 belong to the same transcription factor family, have high sequence homology, and share the same domain structure 59 . This patient responded to a lung cancer regimen that included carboplatin, which is not a standard in RMS, but progressed on subsequent maintenance therapy with pembrolizumab 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical course of the patient described above who responded to radiotherapy followed by ALK inhibition also suggests that these tumors have reduced DNA repair capacity (51). Interestingly, Zein et al reported a patient with RMS carrying an EWSR1-UBP1 fusion, which seems to be a variant of EWSR1-TFCP2, as TFCP2 and UBP1 belong to the same transcription factor family, have high sequence homology, and share the same domain structure (58). This patient responded to a lung cancer regimen that included carboplatin, which is not a standard in RMS, but progressed on subsequent maintenance therapy with pembrolizumab (58).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as the advance of molecular biology technique, especially next-generation sequencing applying for the pathological diagnosis, numerous novel characteristic molecules involving neoplastic diagnosis have been unearthed and thus refined many tumor entities in mesenchymal tumor, such as HEY1-NCOA2 fusion in mesenchymal chondrosarcoma [ 2 ], EWSR1-NR4A3 fusion in extraskeletal myxoid chondrosarcoma [ 3 ], WWTR1-CAMAT1 fusion and YAP1-TFE3 fusion in epithelioid hemangioendothelioma [ 4 , 5 ]. As regard to RMS, PAX3-FOXO1 and PAX7-FOX1 fusion were characteristics in alveolar RMS [ 6 ], and the MYOD1 mutation, EP300-VGLL3, NCOA2-MEIS1, CAV1-MET, YAP1-MAML2, EWSR1-UBP1 fusion in a small subset of spindle cell/sclerosing RMS (SS-RMS) [ 7 11 ]. Most importantly, rare cases of RMS characteristic by the profiling of epithelioid to spindle cells, namely epithelioid and spindle RMS (ES-RMS), were recently found to harbor EWSR1-TFCP2 or FUS-TFCP2 fusion and predominately arising in the bone of head and neck and pelvis, the patients with these RMS have extraordinarily adverse prognosis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%